Participation of NGOs in local development planning the case of the province of South Cotabato - Navarro, Abner H.
Non-Government Organization (NGOs) participation in local development planning has been mandated by the Local Government Code which requires their membership in various local special bodies, foremost of which is the Local Development Council (LCD) where at least 25% of the members are NGOs. However, LCDs have varied number of NGO-members depending on the decisions of this body whether to allow the participation of more NGOs or limit them to the minimum level. In the Provincial Development Council of South Cotabato, there are seventeen (17) accredited NGOs compared to sixteen (16) members from the government. In Koronadal City there are twelve (12) NGOs to thirty-two (32) members from the government and in Lake Sebu, there are nine(9) NGOs compared to twenty-two (22) government representatives. The main purpose of this study is to determine the roles and level of participation, the reasons for their participation and non-participation in local development planning and the level of their representation in the local development councils. The study found out the NGOs tend to be more active in their participation in LCD meetings when they are allowed greater membership because in the Provincial Development Council, they can always muster very good representation compared to Koronadal City and Lake Sebu where NGO members in their respective LDCs were limited to the minimum requirements of the Code. In development planning activities, NGOs gave themselves higher rating in terms of their participation in decision-making procedures compared to LGU officials who thinks that NGOs are only fairly performing.However, LGUs recognize the skills and expertise of NGOs in their respective fields but they think that NGOs are not very good in listening to development concerns presented in planning activities. NGOs also are actively assisting LGUs in disseminating development programs to various communities to ensure that the grassroots also know what their government is doing in terms of delivery of basic services. In addition to this, both LGUs and NGOs are saying that the very reason for continuing participation of NGOs in development planning activities is to forge better partnership and in bringing the voices of the people they serve in the communities to the attention of LGUs. It was further found that the foremost reasons for the non-participation of NGOs in development planning activities is their adversity with Local Executives in terms of political affiliations and their suspicion that their participation in Local Government Unit (LGU)-initiated activities will not be recognized and acceptable.